Multimodal imaging features of primary pericardial synovial sarcoma: a case report - Jin, Hongrui; Zhang, Yong; Zhang, Wenbo; Wang, Keyan (Frontiers in Oncology, 2023)
Background: Primary pericardial synovial sarcoma is an extremely rare malignant tumor, and affected patients have a poor prognosis. Only a few cases have been reported in the literature.A 34-year-old man was admitted to our hospital with chest tightness and a cough. An echocardiogram revealed a heterogeneous mass with a large pericardial effusion. Further computed tomography (CT) of the chest and cardiac magnetic resonance imaging (CMRI) demonstrated an irregular pericardial mass abutting the left atrium and left ventricle and invading the mediastinal structures.Pathology results showed that the tumor was a monophasic synovial sarcoma. The patient underwent chemotherapy and survived for 17 months.Discussion: Many cardiac tumors are clinically asymptomatic or nonspecific, and they are frequently detected or diagnosed at an advanced stage of the disease.Multimodal cardiac imaging facilitates the detection and assessment of cardiac tumors.In particular, CMRI is considered as a superior imaging tool, because it provides high tissue contrast and can detect invasion of the myocardium. We describe the clinical details and multimodal imaging features of a rare primary pericardial synovial sarcoma, hoping to provide guidance for the diagnosis of similar cases in the future.